Characterization of lignocellulolytic activities from fungi isolated from the deep-sea sponge Stelletta normani - Balestrini, Raffaella; Batista García, Ramón Alberto; Sutton, Thomas; Jackson, Stephen A.; Tovar Herrera, Omar Eduardo; Balcázar López, Edgar; Sánchez Carbente, María del Rayo; Sánchez Reyes, Ayixon; Dobson, Alan D. W.; Folch Mallol, Jorge Luis (2017)
Extreme habitats have usually been regarded as a source of microorganisms that possess robust proteins that help enable them to survive in such harsh conditions. The deep sea can be considered an extreme habitat due to low temperatures (<5ÊC) and high pressure, however marine sponges survive in these habitats. While bacteria derived from deep-sea marine sponges have been studied, much less information is available on fungal biodiversity associated with these sponges. Following screening of fourteen fungi isolated from the deep-sea sponge Stelletta normani sampled at a depth of 751 metres, three halotolerant strains (TS2, TS11 and TS12) were identified which displayed high CMCase and xylanase activities. Molecular based taxonomic approaches identified these strains as Cadophora sp. TS2, Emericellopsis sp. TS11 and Pseudogymnoascus sp. TS 12. These three fungi displayed psychrotolerance and halotolerant growth on CMC and xylan as sole carbón sources, with optimal growth rates at 20ÊC. They produced CMCase and xylanase activities, which displayed optimal temperature and pH values of between 50±70ÊC and pH 5±8 respectively, together with good thermostability and halotolerance. In solid-state fermentations TS2, TS11 and TS12 produced CMCases, xylanases and peroxidase/phenol oxidases when grown on corn stover and wheat straw. This is the first time that CMCase, xylanase and peroxidase/phenol oxidase activities have been reported in these three fungal genera isolated from a marine sponge. Given the biochemical characteristics of these ligninolytic enzymes it is likely that they may prove useful in future biomass conversion strategies involving lignocellulosic materials.